A Gold Nanoparticles–Enhanced Carbon Nanotubes Electrochemical Chiral Sensor. Issue 4 (20th January 2017) - Chen, Lisha; Liu, Shuai; Chang, Fengxia; Xie, Xia; Zhu, Zhiwei
Abstract: The field of enantioselective recognition directly using inherently chiral single‐walled carbon nanotubes (cSWCNTs) still remains unexplored. Herein, the insertion of size‐controlled gold nanoparticles (GNPs) to cSWCNTs brings about superior conductivity, high stability, and excellent electrocatalytic ability, thus an enhanced sensitivity for chiral sensing. The practicability of the GNPs/cSWCNTs based electrochemical sensor was validated by chirally recognizing 3, 4‐dihydroxyphenylalanine and tyrosine as model molecules. Abstract :